Fabrication of Rapidly Soluble Zn2+-Releasing Phosphate-Based Glass and Its Incorporation into Dental Resin - Fan Deng; Haruaki Kitagawa; Tomoki Kohno; Tingyi Wu; Naoya Funayama; Pasiree Thongthai; Hefei Li; Gabriela L. Abe; Ranna Kitagawa; Jun-Ichi Sasaki; Satoshi Imazato (Molecules)
Phosphate-based glasses are known for their excellent biocompatibility and adjustable degradation rates. In this study, we fabricated a rapidly soluble zinc-ion-releasing phosphate-based glass (RG) specifically designed for use in dental cavity liners. The aim of this study was to evaluate the ion-releasing properties and antibacterial effects of RG. Additionally, a dental resin incorporating RG was fabricated to serve as a cavity liner, and its effectiveness was investigated in vitro. The RG formulation exhibited high solubility and released high concentrations of Zn2+ at various pH values. To assess the antibacterial properties of RG, six bacterial species detected in deep carious regions were incubated in the presence of RG. In vitro antibacterial testing against six bacterial species revealed that RG exhibited strong bactericidal effects against these prevalent bacteria. Furthermore, using a dentin model infected with Lactobacillus casei or Streptococcus mutans, the experimental resin containing RG demonstrated an effective bactericidal effect in the dentinal tubules, highlighting its potential as a promising material for cavity liners or pulp-capping applications.